Trial-in-Progress: Frontline Brentuximab Vedotin and CHP (A+CHP) in Patients with Peripheral T-Cell Lymphoma with Less Than 10% CD30 Expression - Jagadeesh, Deepa; Sims, Robert B.; Horwitz, Steven M. (Blood, 2020)
Background In the ECHELON-2 phase 3 clinical trial, brentuximab vedotin, cyclophosphamide, doxorubicin, and prednisone (A+CHP) showed clinically meaningful and statistically significant efficacy in patients with peripheral T-cell lymphoma (PTCL) across a range of CD30 expression levels, including the lowest eligible level of 10% by IHC. In addition to the ECHELON-2 study, response data are available from an additional 344 subjects with CD30-expressing PTCL and other large-cell lymphomas (including angioimmunoblastic T-cell lymphoma and peripheral T-cell lymphoma-NOS) who had been treated in studies with brentuximab vedotin as a single agent or in combination with chemotherapy, in both frontline and relapsed/refractory settings. Among these 344 subjects, 184 had tumors with CD30 expression <10% by local assessment, including 83/184 with undetectable CD30 by immunohistochemistry (CD30=0). Responses to brentuximab vedotin have been observed at all levels of CD30 expression, including in tumors with undetectable CD30 levels (Advani 2019; Horwitz 2019). It is hypothesized that A+CHP will demonstrate efficacy in subjects with PTCL and CD30 expression <10% because: i) brentuximab vedotin has shown activity in lymphomas with low CD30 expression; and ii) the activity of CHP chemotherapy in PTCL is unrelated to CD30 expression. This study will include subjects with PTCL subtypes other than systemic anaplastic large cell lymphoma (sALCL). Study Design and Methods This is a dual-cohort, open-label, multicenter, phase 2 clinical trial designed to evaluate the efficacy and safety of A+CHP in subjects with non-sALCL PTCL and CD30 expression <10% on tumor cells. Enrollment will be based on CD30 expression per local lab assessment. Subjects will be assigned to 1 of 2 cohorts based on CD30 expression; up to approximately 40 subjects will be enrolled in the CD30 negative (expression <1%) cohort and approximately 40 subjects will be enrolled in the CD30 positive (expression ≥1% to <10%) cohort. An archived tumor biopsy specimen will be submitted to a central pathology lab for confirmation of CD30 expression. Only subjects with CD30 expression <10% per central confirmation will be analyzed for the primary and secondary endpoints. Subjects will receive 21-day cycles of A+CHP for a target of 6-8 cycles. The primary endpoint of this trial is objective response rate (ORR) per blinded independent central review (BICR). Key secondary endpoints include CR and PFS per BICR and overall survival. Key inclusion criteria include the following: subjects aged 18 years and older with newly diagnosed PTCL, excluding sALCL, per the WHO 2016 classification; CD30 expression <10% by local assessment; and fluorodeoxyglucose-avid disease by PET and measurable disease of at least 1.5 cm by CT, as assessed by the site radiologist. Lymphoma response and progression will be assessed by BICR using Revised Response Criteria for Malignant Lymphoma and modified Lugano criteria. A CT scan will be performed at the time of suspected clinical progression. Subsequent restage assessments (CT scans only) will be performed according to the calendar, relative to the first dose of study treatment, to ensure that tumor progression is uniformly assessed between the treatment arms. Efficacy and safety endpoints will be summarized with descriptive statistics by cohort, with the CD30 negative cohort and the CD30 positive cohort. The summary of overall (CD30 negative and positive cohort combined) may be presented as appropriate. Descriptive statistics (mean, median, standard deviation, minimum, and maximum) will be used to describe continuous variables. Time-to-event endpoints, such as PFS, will be estimated using Kaplan-Meier methodology and Kaplan-Meier plots will be presented. Medians for time-to-event analyses (eg, median PFS), will be presented and two-sided 95% confidence intervals will be calculated using the log-log transformation method. The trial will have sites open in the US and multiple countries in Europe, with enrollment planning to begin in September 2020. Jagadeesh:Verastem: Membership on an entity's Board of Directors or advisory committees; Seattle Genetics: Membership on an entity's Board of Directors or advisory committees, Research Funding; MEI Pharma: Research Funding; Debiopharm Group: Research Funding; Regeneron: Research Funding. Sims:Seattle Genetics, Inc.: Current Employment, Current equity holder in publicly-traded company, Other: Travel expenses. Horwitz:ASTEX: Consultancy; Millenium/Takeda: Consultancy, Research Funding; Corvus: Consultancy; Innate Pharma: Consultancy; Mundipharma: Consultancy; Seattle Genetics: Consultancy, Research Funding; Trillium: Consultancy, Research Funding; Forty Seven: Consultancy, Research Funding; Infinity/Verastem: Research Funding; Celgene: Consultancy, Research Funding; GlaxoSmithKline: Consultancy; Aileron: Consultancy, Research Funding; ADCT Therapeutics: Consultancy, Research Funding; Janssen: Consultancy; Myeloid Therapeutics: Consultancy; Verastem: Consultancy, Research Funding; Vividion Therapeutics: Consultancy; Affirmed: Consultancy; Kura Oncology: Consultancy; Miragen: Consultancy; Kyowa Hakka Kirin: Consultancy, Research Funding; Beigene: Consultancy; C4 Therapeutics: Consultancy; Daiichi Sankyo: Research Funding; Portola: Consultancy, Research Funding.